Study of Zno:Ga Thin Film Structure With Variation of Plasma Power Using the DC Magnetron Sputtering Method - Putut Marwoto; Budi Astuti; Sugianto Sugianto (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
ZnO:Ga thin films grown on a corning glass substrate by the DC Magnetron Sputtering method have been successfully grown. The purpose of this study was to study the effect of plasma power on the resulting thin film structure. The quality and structure of the films were studied using X-ray duffraction (XRD), and scanning electron microscopy (SEM). Based on XRD characterization, it was found that the ZnO:Ga thin film has a hexagonal wurtize structure on the C-axis with orientation planes (002) and (101). The quality of the resulting thin films can also be seen from the value of full-width at half maximum (FWHM) in the orientation plane (002) which increases with increasing plasma power during the growth process from 0.13°- 0.16°. The larger the FWHM value, the smaller the crystal grain size so that the structure becomes less good. This is supported by the surface morphology of the film which is less dense when the plasma power increases. ©2018 JNSMR UIN Walisongo. All rights reserved.